The efficacy of tourniquets as a first-aid measure for Russell's viper bites in Burma. - Tun-Pe; Tin-Nu-Swe; Myint-Lwin; Warrell, D; Than-Win (1987)
The efficacy of the tourniquets commonly used by Russell's viper bite victims in retarding venom movement from the bite was studied in 37 cases by measuring venom antigen levels by enzyme-linked immunosorbent assay in venous samples taken proximal and distal to the tourniquets and also before and after release of tourniquets. In most cases, the tourniquet did not prevent proximal spread of venom. In 8/37 cases, however, venom antigen assays suggested but did not prove that venom absorption was being delayed by the tourniquet.